2002
DOI: 10.1002/jmri.10194
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative evaluation of patients awaiting liver transplantation: Comparison of multiphasic contrast‐enhanced 3D magnetic resonance to helical computed tomography examinations

Abstract: Purpose:To determine the feasibility of using a multiphasic magnetic resonance (MR) examination to evaluate the hepatic arterial anatomy and parenchyma in patients awaiting orthotopic liver transplantation (OLT). Materials and Methods:Twenty consecutive patients awaiting OLT underwent multiphasic MR (using a T1-weighted 3D gadolinium-enhanced gradient-echo (GRE) sequence and two separate injections of contrast material) and computed tomography (CT) imaging; both imaging studies were performed within a 1-week p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 34 publications
(49 reference statements)
0
12
0
3
Order By: Relevance
“…A strength of the current study is that compared with other studies, it includes a larger number of patients who underwent liver transplantation, and findings on MRI were correlated with findings on explant 9, 18. Limitations of our study include a variable, and in some cases lengthy, time interval between the last MRI and surgery, and relatively few patients with PVT.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A strength of the current study is that compared with other studies, it includes a larger number of patients who underwent liver transplantation, and findings on MRI were correlated with findings on explant 9, 18. Limitations of our study include a variable, and in some cases lengthy, time interval between the last MRI and surgery, and relatively few patients with PVT.…”
Section: Discussionmentioning
confidence: 98%
“…The experience gained with living related donor procedures has demonstrated that MRI is extremely accurate at evaluating the parenchyma for liver masses as well as the venous, arterial, and biliary trees 8. Moreover, MRI can be performed in patients with renal impairment, a frequent complication in cirrhotic patients 9. Data regarding the sensitivity and specificity of MRI at detecting and characterizing portal vein thrombi are scarce 10.…”
mentioning
confidence: 99%
“…Although the spatial resolution of MRI for the evaluation of hepatic arterial anatomy remains inferior to that of DSA, MRA has, in our experience, proven to be an accurate preoperative test for the definition of the portal and hepatic venous anatomy. Several studies have found that CT or MRI can show the anatomy of the hepatic vasculature of a liver donor before transplantation [23][24][25]. Winter et al [23] and Chan et al [24] showed that in liver transplantation candidates, successful 3D CT arteriography was as accurate as catheter angiography for assessing hepatic arterial anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…By replacing CT with MRI, we can eliminate the need to expose the potential donor to ionizing radiation and less safe contrast agents than gadolinium chelates (9, 13). Eubank et al (10) reported that classification of the hepatic arterial anatomy by CTA and MRA was concordant in 85% (17/20) of patients, and discordant in 15% (3/20) of patients awaiting orthotopic liver transplantation. Schroeder et al (14) undertook a study comparing CT and MR for the preoperative evaluation of potential living liver donors ( N = 25).…”
Section: Discussionmentioning
confidence: 99%
“…With rapid technological developments in magnetic resonance imaging (MRI), such as increased gradient strength, surface coils with better sensitivity, and parallel imaging, MR angiography (MRA) has recently become a new imaging modality for the preoperative evaluation of potential living liver donors. It has been proven to be a useful alternative to CTA in patients with impaired renal function (9–13). Furthermore, an MR examination has additional benefits compared to CTA in the preoperative workup of liver donors, including no radiation hazard and the ability to reveal the biliary anatomy without using a biliary contrast agent.…”
mentioning
confidence: 99%